INDOMETHACIN TEST USAGE AT UNITED KINGDOM TERTIARY CENTRES OVER 20 YEARS-AN AUDIT. Issue 11 (14th October 2015) - Bose, Pyari; Palethorpe, DG; Marin, J; Nesbitt, A; Lowe, J; Goadsby, PJ
Abstract : Background: Indomethacin-responsive trigeminal autonomic cephalalagias (TACS), paroxysmal hemicrania (PH) and hemicrania continua (HC), are unique, important syndromes to understand. Aim: Evaluation of the role of the placebo-controlled indomethacin test (P-Indotest) in the diagnosis of primary headache disorders. Method: Patients notes, clinic letters and headache diaries of patients under our care (PJG) over a 20 year period across various UK Neurology tertiary care centres were examined to obtain data against an audit collection tool. A pre-determined set of data were extracted, and the test procedure reviewed for compliance against a standard with minimum data set requirement by an unblinded observer. The original test score was noted, and prospectively re-scored by a blinded observer. Results: Patients (n=7; 4 female) were aged from 24 to 51 years. The majority (85%) had side locked headache. P-Indotest was positive in 78% of the cases with patients having either HC or PH. Of all patients tested, 42% had unilateral photophobia and phonophobia and all these cases had a positive response. No serious adverse events were noted. Sleepiness was often reported on the active treatment as was transient worsening of headache in unilateral chronic migraine. Further data is being compiled. Conclusion: The P-IndoTest is a reliable and safe test and should in the diagnosis of patients with possible indomethacin sensitive TACs. While far from ideal, a positive indomethacin test does identify a particular biology and should be retained as a diagnostic marker of PH and HC until its basis is understood.